THE EFFECT OF THE IMPLEMENTATION OF PSAK 65 ON FINANCIAL PERFORMANCE - Agung Setya Nugraha; Totok Dewayanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to determine the effect of accounting standards on financial performance in the performance of companies in the manufacturing sector listed on the Indonesia Stock Exchange in 2015-2019. The data used in this study are secondary data. The method in selecting the sample is purposive sampling. The number of samples in this study was 471 companies. Hypothesis testing in this study was carried out using the t statistical test. The data analysis technique used in this study is multiple linear regression analysis and moderated regression analysis using the Statistical Product and Service Solution (SPSS) version 25 for windows data processing software program. The results of this study indicate that accounting standards have a positive and significant effect on financial performance with a correlation value of 0. Keywords: accounting standards, financial performance.